Khrushchev's cold summer: Gulag returnees, crime, and the fate of reform after Stalin - Dobson, Miriam (Cornell Univ. Press, 2009)
1953 : "the most painful year" -- Prisoners and the art of petitioning, 1953-1956 -- Heroes, enemies, and the secret speech -- Returnees, crime, and the gulag subculture -- The redemptive mission -- A return to weeding -- 1961 : clearing a path to the future -- Literary hooligans and parasites